Effect of α-amylase digestion in fermented Nagara bean grits for gelatinization profile and in vitro starch digestibility. Issue 1 (February 2020) - Susi,; Agustina, L; Gendrosari, S
Abstract: Treatment of α -amylase digestion in wet grits nagara bean after spontaneous fermentation was assessed to determine changes in rehydration ability, gelatinization profile and in vitro starch digestibility of the flour produced. This was important for further processed products that required easy hydration in cold water and high starch digestibility. The research was carried out by hydrolysis of α -amylase with 60 IU enzyme activity as much as 0.1% on wet grits nagara beans from spontaneous fermentation which had been soaked in NaHSO3 and Ca(OH)2 for 1 hour. Moreover, α -amylase digestion was carried out at 37°C for 30, 60 and 90 minutes. The results showed that the amylose content of nagara bean flour from the pre-treatment soaking using Ca(OH)2 was relatively higher than the pre-treatment of NaHSO3, and there was a tendency for amylase digestion up to 90 minutes could reduce amylose and starch content. In vitro starch digestibility of flour by amylase digestion of wet grits nagara bean for 60 minutes with pre-treatment soaked in Ca(OH)2 were 88.79% db, peak viscosity and final viscosity of 2416 cP and 2419 cP respectively.